Avaliação da sensibilidade de organismos aquáticos e terrestres ao triclopyr - Bastos, Joani Cristina Húngaro Aires da Gama [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Improper use of herbicides such as triclopyr may generate residues in soil and water that can endanger the balance of the environment. To understand the effects of this herbicide in the environment, this aims to classify the triclopyr for its acute toxicity to five aquatic species, select non-target species for the environmental monitoring of this molecule based on three environmental poisoning risk ratings, select plants indicators of the presence of herbicide residues in the soil and if it is safe to be used for controlling weeds. For acute toxicity to non-target organisms were conducted acute toxicity tests with the Mato Grosso (Hyphessobycon eques), snail (Pomacea canaliculata), Azolla caroliniana, Lemna minor and Daphnia magna. The risk of environmental poisoning has been classified according to three classifications, which was calculated by dividing the value of the estimated environmental concentration (mg L-1) and the CL50 or CE50 (mg L -1) for each non-target organism. For their presence in the soil tests were conducted at room acclimatized to the species Cucumber (Cucumis sativus), tomato (Solanum lycopersicum) and radish (Raphanus sativus) at concentrations of 0.0; 0.5 1.0; 2.5; 5.0 and 7.5 mg L-1, the evaluation of the phytotoxicity of the plants were carried out on the 3rd, 7th, 11th and 14th day after application and after 14 days an assessment was made of plant height and total dry matter. Assessing the effectiveness of triclopyr was conducted in a greenhouse, the doses used were 0.0; 0.5; 1.0; 2.0; 3.0 and 4.0 L ha-1, and species used were Myriofyllum aquaticum, Nymphoide indica and Limnobium laevigatum. The CL50 and CE50 for 48h triclopyr was 0.61 and 0.62 mg L-1 for H. eques and D. magna respectively, P. canaliculata, A. caroliniana and L. minor CE50, 7 days were 4.67; 10.52 and 6.95 mg L-1, respectively, ranking as moderately toxic to L. minor, A. caroliniana and P. canaliculata as high or highly toxic to H. eques ...

O uso inadequado de herbicidas como o triclopyr pode gerar resíduos no solo e na água que podem colocar em risco o equilíbrio do meio ambiente. Para compreender os efeitos deste herbicida no meio ambiente, o presente tem como objetivo classificar o triclopyr pela sua toxicidade aguda para cinco espécies aquáticas, selecionar espécies não alvo para o monitoramento ambiental desta molécula com base em três classificações de risco de intoxicação ambiental, selecionar plantas indicadores da presença de resíduos do herbicida no solo e se ele é seguro para ser utilizado no controle de macrófitas. Para a toxicidade aguda de organismos não alvos, foram realizados ensaios de toxicidade aguda com o mato grosso (Hypessobrycon eques), caramujo (Pomacea canaliculata), Azolla caroliniana, Lemna minor e Daphnia magna. O risco de intoxicação ambiental foi classificado de acordo com três classificações, que foi calculado pela divisão entre o valor da concentração ambiental estimada (mg L-1) e pela CL50 ou CE50 (mg L -1) para cada organismo não alvo. Para a sua presença no solo foram realizados ensaios em sala aclimatada com as espécies pepino (Cucumis sativus), tomate (Solanum lycopersicum) e rabanete (Raphanus sativus) nas concentrações de 0,0; 0,5 1,0; 2,5; 5,0 e 7,5 mg L-1, a avaliação da fitotoxicidade das plantas foram realizadas no 3º, 7º, 11º e 14º dia após aplicação e no 14º dia foi realizada a avaliação da altura das plantas e matéria seca total. A avaliação da eficácia do triclopyr foi realizada em casa de vegetação, as doses utilizadas foram 0,0; 0,5; 1,0; 2,0; 3,0 e 4,0 L ha-1, as espécies utilizadas foram Myriofyllum aquaticum, Nymphoide indica e Limnobium laevigatum. A Cl50 e CE50, 48h para o triclopyr foi de 0,61 e 0,62 mg L-1 para H. eques e D. magna respectivamente, para P. canaliculata, A. caroliniana e L. minor a CE50, 7 dias foram de 4,67; 10,52 e 6,95 mg L-1, respectivamente...
Keywords: Indicadores biológicos; Herbicidas; Resíduos; Toxicidade Aguda; Toxicidade - Testes; Indicators (Biology)